Active Control of the THz Wave Polarization State by an Electronically Controlled Graphene Composite Metasurface - Wang, Guocui; Hu, Bin; Khan, Muhammad Ismail; Zhang, Yan (Frontiers in Physics, 2021)
Active control of terahertz (THz) wave polarization state is of great significance for sensitive detection, imaging and communication. Here, a tunable THz quarter wave plate is designed by electronically controlling a composite metasurface consisting of gold cross antennas and a monolayer graphene. The graphene composite metasurface acts as a quarter-wave plate when the chemical potential of graphene is 0 eV, by which the polarization state of the incident THz wave is converted from linear polarization to circular polarization. After the chemical potential of graphene is increased to 0.5 eV, the transmitted polarization state of the THz wave is gradually changed from right circular polarization to right elliptical polarization, and to linear polarization. Furthermore, the polarization state of the THz wave is able to be changed from left circular polarization to left elliptical polarization, and to linear polarization if the device is clockwise rotated by 90°. Therefore, the polarization of a THz wave could be actively controlled by the proposed tunable THz quarter wave plate. Our work will offer a new avenue for tunable THz polarize modulation devices.